How Sanctions Work: Iran and the Impact of Economic Warfare - Elliott, Kimberly Ann (Journal of Economic Literature, 2024)
Kimberly Ann Elliott of Former Senior Fellow with the Peterson Institute and the Center for Global Development reviews “How Sanctions Work: Iran and the Impact of Economic Warfare” by Narges Bajoghli, Vali Nasr, Djavad Salehi-Isfahani, and Ali Vaez. The Econlit abstract of this book begins: “Explores how sanctions have impacted the political calculus of those in power in Iran, providing a fuller picture of how prolonged comprehensive sanctions both impact the targeted society and reverberate outward into international politics and economics.”